DC inline plane test of silicone rubber samples with different filler for high-voltage insulation - Nurbahirah Norddin; Intan Mastura Saadon; Najwa Kamarudin; Norain Rahim; Jeefferie bin Abd Razak (Institute of Advanced Engineering and Science, 2020)
This paper is about preparation of silicone rubber (SiR) samples with different filler for high-voltage insulation purpose. The fillers used were silica from waste glass, calcium carbonate from cockle shell, silica/calcium carbonate and wollastonite. All the fillers were crushed into powder and undergo internal mixer and hot press as a material preparation. It was expected that the combination of filler with silicone rubber would give better result when experiencing ageing process. The direct current (DC) inclined plane test was used to investigate the tracking and erosion on silicone rubber composites. The tracking length was observed between the top and bottom electrode. Comparison would then be made between the silicone rubbers with different fillers based on the result obtained from the experiment.